Abundance, viability and diversity of the indigenous microbial populations at different depths of the NEEM Greenland ice core - Vanya Miteva; Kaitlyn Rinehold; Todd Sowers; Aswathy Sebastian; Jean Brenchley (Polar Research, 2015)
The 2537-m-deep North Greenland Eemian Ice Drilling (NEEM) core provided a first-time opportunity to perform extensive microbiological analyses on selected, recently drilled ice core samples representing different depths, ages, ice structures, deposition climates and ionic compositions. Here, we applied cultivation, small subunit (SSU) rRNA gene clone library construction and Illumina next-generation sequencing (NGS) targeting the V4–V5 region, to examine the microbial abundance, viability and diversity in five decontaminated NEEM samples from selected depths (101.2, 633.05, 643.5, 1729.75 and 2051.5 m) deposited 300–80 000 years ago. These comparisons of the indigenous glacial microbial populations in the ice samples detected significant spatial and temporal variations. Major findings include: (a) different phylogenetic diversity of isolates, dominated by Actinobacteria and fungi, compared to the culture-independent diversity, in which Proteobacteria and Firmicutes were more frequent; (b) cultivation of a novel alphaproteobacterium; (c) dominance of Cyanobacteria among the SSU rRNA gene clones from the 1729.75-m ice; (d) identification of Archaea by NGS that are rarely detected in glacial ice; (e) detection of one or two dominant but different genera among the NGS sequences from each sample; (f) finding dominance of Planococcaceae over Bacillaceae among Firmicutes in the brittle and the 2051.5-m ice. The overall beta diversity between the studied ice core samples examined at the phylum/class level for each approach showed that the population structure of the brittle ice was significantly different from the two deep clathrated ice samples and the shallow ice core.